Elliot Sober & David Sloan Wilson unto others. The evolution and psychology of unselfish behavior. Cambridge, ma./London: Harvard University press, 1998. 394 p. isbn 0-674- 93047-9. - Alejandro Rosas (Ideas y Valores)
-